1992
DOI: 10.1073/pnas.89.12.5286
|View full text |Cite
|
Sign up to set email alerts
|

Potent and selective inhibition of human immunodeficiency virus (HIV)-1 and HIV-2 replication by a class of bicyclams interacting with a viral uncoating event.

Abstract: A series of bicyclams have been shown to be potent and selective inhibitors of human immunodeficiency virus (HIV). The compounds are inhibitory to the replication of various HIV-1 and HIV-2 strains in various human T-cell systems, including peripheral blood lymphocytes, at 0.14-1.4 microM, without being toxic to the host cells at 2.2 mM. The bicyclam JM2763 is active against 3'-azido-3'-deoxythymidine (zidovudine; AZT)-resistant HIV-1 strains and acts additively with AZT. Mechanism of action studies revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
186
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(189 citation statements)
references
References 43 publications
3
186
0
Order By: Relevance
“…We previously described a class of low-molecularweight compounds, called bicyclams, that strongly inhibit the replication of X4 HIV-1 and HIV-2 in the nanomolar concentration range (17)(18)(19). We demonstrated that the selective anti-HIV activity of the bicyclams against CXCR4-using virus strains results from a specific interaction of the compounds with the CXC-chemokine receptor CXCR4 (20 -22).…”
Section: Discussionmentioning
confidence: 99%
“…We previously described a class of low-molecularweight compounds, called bicyclams, that strongly inhibit the replication of X4 HIV-1 and HIV-2 in the nanomolar concentration range (17)(18)(19). We demonstrated that the selective anti-HIV activity of the bicyclams against CXCR4-using virus strains results from a specific interaction of the compounds with the CXC-chemokine receptor CXCR4 (20 -22).…”
Section: Discussionmentioning
confidence: 99%
“…85 AMD3100 was initially considered to interfere with HIV-1 fusion or uncoating. 63 Initially developed at Johnson Matthey in collaboration with the Rega Institute for Medical Research (Leuven University, Leuven, Belgium), this compound was first called JM3100, which changed to AMD3100 after a new company (AnorMED, Langley, BC, Canada) took over the development. The anti-HIV-1 activity of AMD3100, restricted to X4-HIV-1 strains, and the blocking function of AMD3100 on gp120 interaction with CXCR4 during viral entry 86 were the initial focus during the early development of this drug.…”
Section: Non-peptide Cxcr4 Antagonistsmentioning
confidence: 99%
“…1) have been identified as potent inhibitors of human immunodeficiency virus (HIV) 1 type 1 and type 2 replication (1). The lead compound of the bicyclam series was discovered as an impurity being responsible for the antiviral effect in a preparation of cyclam (2).…”
mentioning
confidence: 99%
“…The structure-function relationship with respect to the antiviral effect of the bicyclams has been worked out in great detail by De Clercq et al (1) and Bridger et al (2, 9 -11). The optimum structural features required for potent antiviral activity of "bicyclam" analogs include the presence of two azamacrocyclic rings containing 12-14 atoms/ring and a meta-or para-substituted phenylenebismethylene linker (para more active than meta) connecting the macrocyclic rings at nitrogen positions.…”
mentioning
confidence: 99%